The Barn. (September 2014) - Lingelbach, Bernd
A short history of the Barn is given, including the description of a few objects. The Barn is a well-known 'hands-on' museum; two examples are given to show that from time to time something new is presented. Prior to the 2009 European Conference on Visual Perception in Regensburg, a conference called '3-Dillusions' was held in the Barn. Owing to the success of that meeting the conference, 'Illusions and Delusions' was held in August 2013.